Chromatic discrimination measures in mature observers depend on the response window - Fars, Julien; Fernandes, Thiago P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (Scientific Reports, 2022)
Our past anecdotal evidence prompted that a longer response window (RW) in the Trivector test (Cambridge Colour Test) improved mature observers' estimates of chromatic discrimination. Here, we systematically explored whether RW variation affects chromatic discrimination thresholds measured by the length of Protan, Deutan and Tritan vectors. We employed the Trivector test with three RWs: 3 s, 5 s, and 8 s. Data of 30 healthy normal trichromats were stratified as age groups: 'young' (20-29 years), 'middle-aged' (31-48 years), and 'mature' (57-64 years). We found that for the 'young' and 'middle-aged', the thresholds were comparable at all tested RWs. However, the RW effect was apparent for the 'mature' observers: their Protan and Tritan thresholds decreased at 8-s RW compared to 3-s RW; moreover, their Tritan threshold decreased at 5-s RW compared to 3-s RW. Elevated discrimination thresholds at shorter RWs imply that for accurate performance, older observers require longer stimulus exposure and are indicative of ageing effects manifested by an increase in critical processing duration. Acknowledging low numbers in our 'middle-aged' and 'mature' samples, we consider our study as pilot. Nonetheless, our findings encourage us to advocate a RW extension in the Trivector protocol for testing mature observers, to ensure veridical measures of their chromatic discrimination by disentangling these from other ageing effects-slowing down of both motor responses and visual processing.
CRIS-Team WoS Importer:2022-06-17